Trumpet technique - Campos, Frank Gabriel (Oxford University Press, 2005)
Trumpet Technique' is a resource for performers, teachers, and students seeking to develop the highest level of skill. The author, a trumpet professor and performer, applies the latest developments in physiology, psychology, learning theory and psychomotor research to brass technique and performance.